Altruism and the Link to Pro-social Pandemic Behavior - Neumann-Böhme, Sebastian; Sabat, Iryna; Attema, Arthur E. (Frontiers in Health Services, 2022)
In the Corona pandemic, especially in the phase before vaccines were available, people's risk of infection with COVID-19 was dependent on the adherence to pandemic behaviors (e. g., wearing masks) of others around them. To explore whether altruistic individuals are more likely to engage in pro-social behaviors to protect others during the pandemic, we use data from the European COVID Survey (ECOS). The data was collected in September 2020 and consisted of a representative sample from seven European countries (N = 7,025). Altruism was measured as a deviation from purely self-interested behavior by asking respondents how much they would be willing to donate from an unexpected gain to the equivalent of 1000€. Respondents who were willing to donate more than 0 Euros (68.7%) were treated as altruistic; on average, respondents were willing to donate 11.7% (SD 17.9) of the gain. Controlling for country, sociodemographics, general risk aversion and COVID-specific risk aversion, we find that individuals classified as altruistic were more likely to behave pro-socially. More specifically, we find that altruistic respondents were more likely to wait at home for test results and wear a mask where it is recommended. They would also stay about 1 day longer under quarantine without symptoms after visiting a high-risk country and were less likely to go to a supermarket with COVID symptoms. We find no significant effect for wearing a mask in places where it is mandatory and for inviting more than six people into the house. Furthermore, we find that the subjective risk assessment of COVID-19 also plays a role in these behaviors. Our results support evidence from the literature that suggests that adherence to pro-social pandemic behaviors may be increased if public health officials emphasize the altruistic nature of these behaviors.